2017
DOI: 10.1093/ofid/ofx004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cryptococcosis and Cryptococcal Meningitis in a Large Retrospective Cohort of Patients After Solid Organ Transplantation

Abstract: Background.Cryptococcosis is the third most common invasive fungal infection in solid organ transplant (SOT) recipients. There are no nationally representative data describing the incidence, risk factors, and outcomes of cryptococcosis after SOT.Methods.We assembled a large cohort of adult SOT recipients using Classification of Diseases, Ninth Revision, Clinical Modification billing data from Healthcare Cost and Utilization Project State Inpatient Databases of Florida (2006–2012), New York (2006–2011), and Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 21 publications
4
60
1
2
Order By: Relevance
“…Over the course of 13 years, 0.8% of renal transplant recipients developed cryptococcosis, and most occurred a long time after transplantation. The incidence of cryptococcosis in renal transplant recipients observed in this study was similar to the low incidence rates reported by other groups (0.3%‐5.5%), but with high mortality . Among these 47 patients, the majority had received AMBd (87.2%) as first‐line therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Over the course of 13 years, 0.8% of renal transplant recipients developed cryptococcosis, and most occurred a long time after transplantation. The incidence of cryptococcosis in renal transplant recipients observed in this study was similar to the low incidence rates reported by other groups (0.3%‐5.5%), but with high mortality . Among these 47 patients, the majority had received AMBd (87.2%) as first‐line therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Cryptococcosis is specifically recognized as the second most common invasive fungal infection in renal transplant recipients in many countries, including Brazil, with incidence rates ranging from 0.3% to 5.5% and overall mortality rates as high as 20%‐50% have been reported . Amphotericin B formulations are considered the best option for primary therapy and the 2010 IDSA Guidelines recommend lipid formulations of amphotericin B .…”
Section: Introductionmentioning
confidence: 99%
“…The detection of CrAg was greatly improved with the advent of point-of-care diagnostic assays, such as a lateral flow assay for use in serum and other sample types — including whole blood from finger stick samples [10]. However, a “screen and treat” approach based on testing for cryptococcal antigenemia followed by preemptive administration of antifungals is not part of standard practice in non-HIV infected patients [3], while it is a consolidated practice in resource-limiting settings with high incidence of HIV and cryptococcal diseases [14].…”
Section: Discussionmentioning
confidence: 99%
“…As currently understood, with the advent of effective antiretroviral therapy, the majority of cryptococcosis cases in nations as ours occurs among non-HIV-infected patients [2], especially in those who have a co-existing immunocompromised state [3]. In these patients, lack of suspicion for, and/or delay in diagnosis of cryptococcosis may increase the likelihood of unfavorable outcome [4].…”
Section: Introductionmentioning
confidence: 97%
“…Given the exposure of the allograft to the external environment, lung transplant (LTx) recipients might be considered to have the highest risk of cryptococcosis compared with other SOT recipients . Despite this, relatively little is known about cryptococcal infection in this group of patients.…”
Section: Introductionmentioning
confidence: 99%